Capacity building and participatory innovation: experience with small livestock producers in the state of Sonora, Mexico (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2015)
Livestock Services Centers (CSG) promote the organization and coordination of small livestock producers under a common strategy for standardization of quality, cost reduction and market research through the provision of comprehensive technical assistance, which are grouped on two axes: Organizational Development and Technological Development. The aim was to strengthen the technical and administrative capacities to improve their economic productive and organizational processes units. Methodologically, is to form groups of 30 livestock producers with production characteristics and similar management, as well as geographically close, each CSG attending a provider of professional services (PSP) with a technical background in the area of animal husbandry and in two cases PSP with a business profile. As a result they were integrated to 913 producers in 26 municipalities, of Rural Development Districts (DDR) of Agua Prieta, Magdalena Montezuma, Hermosillo, Ures, Mazatán, Guaymas, Cajeme and Navojoa, all from the state of Sonora, México.
Keywords: development of capabilities; public policy; ranching; territorial development strategy; technological innovation